Evaluation of plasma cytokines in patients with cocaine use disorders in abstinence identifies transforming growth factor alpha (TGFα) as a potential biomarker of consumption and dual diagnosis - Maza-Quiroga, Rosa; García-Marchena, Nuria; Romero-Sanchiz, Pablo; Barrios, Vicente; Pedraz, María; Serrano, Antonia; Nogueira-Arjona, Raquel; Ruiz, Juan Jesus; Soria, Maribel; Campos, Rafael; Chowen, Julie Ann; Argente, Jesus; et al. (PeerJ, 2017)
Background Cocaine use disorder (CUD) is a complex health condition, especially when it is accompanied by comorbid psychiatric disorders (dual diagnosis). Dual diagnosis is associated with difficulties in the stratification and treatment of patients. One of the major challenges in clinical practice of addiction psychiatry is the lack of objective biological markers that indicate the degree of consumption, severity of addiction, level of toxicity and response to treatment in patients with CUD. These potential biomarkers would be fundamental players in the diagnosis, stratification, prognosis and therapeutic orientation in addiction. Due to growing evidence of the involvement of the immune system in addiction and psychiatric disorders, we tested the hypothesis that patients with CUD in abstinence might have altered circulating levels of signaling proteins related to systemic inflammation. Methods The study was designed as a cross-sectional study of CUD treatment-seeking patients. These patients were recruited from outpatient programs in the province of Malaga (Spain). The study was performed with a total of 160 white Caucasian subjects, who were divided into the following groups: patients diagnosed with CUD in abstinence (N = 79, cocaine group) and matched control subjects (N = 81, control group). Participants were clinically evaluated with the diagnostic interview PRISM according to the DSM-IV-TR, and blood samples were collected for the determination of chemokine C-C motif ligand 11 (CCL11, eotaxin-1), interferon gamma (IFNγ), interleukin-4 (IL-4), interleukin-8 (IL-8), interleukin-17α (IL-17α), macrophage inflammatory protein 1α (MIP-1α) and transforming growth factor α (TGFα) levels in the plasma. Clinical and biochemical data were analyzed in order to find relationships between variables. Results While 57% of patients with CUD were diagnosed with dual diagnosis, approximately 73% of patients had other substance use disorders. Cocaine patients displayed greater cocaine symptom severity when they were diagnosed with psychiatric comorbidity. Regarding inflammatory factors, we observed significantly lower plasma levels of IL-17α (p < 0.001), MIP-1α (p < 0.001) and TGFα (p < 0.05) in the cocaine group compared with the levels in the control group. Finally, there was a significant primary effect of dual diagnosis on the plasma concentrations of TGFα (p < 0.05) in the cocaine group, and these levels were lower in patients with dual diagnoses Discussion IL-17α, MIP-1α and TGFα levels are different between the cocaine and control groups, and TGFα levels facilitate the identification of patients with dual diagnosis. Because TGFα reduction is associated with enhanced responses to cocaine in preclinical models, we propose TGFα as a potential biomarker of complex CUD in humans.
Keywords: Cocaine use disorders; Cytokines; Dual diagnosis